Margaret Mitchell [videorecording (DVD)] : American rebel - White, Kathy; Roberts, Pamela (Filmmaker) (PBS Distribution, 2012)
Tells the compelling story of the author's life. Through dramatic reenactments and interviews with top Mitchell scholars, Margaret Mitchell emerges as a complex and fascinating woman who had much in common with her iconic creation, Scarlett O'Hara.